Negative Knowledge - Hüsch, Sebastian; Koch, Isabelle; Thomas, Philipp (Basler Studien zur Philosophie, 2020)
The advent of Modernity was accompanied by a radical criticism of traditional metaphysics. In particular since the 20th century, rationality is predominantly conceived of as positivistic and scientistic, reducing reality to what is positively knowable. The price to pay is the cutting out of any kind of phenomenon of negativity. The present volume explicitly explores the philosophical and epistemological potential of negativity. The contributions brought together in this book tackle the question of negativity from historical as well as from systematical perspectives. From different angles, they defend the claim that philosophical approaches recurring to negativity can build a non-reductive conceptualization of rationality, and thus offer a valuable contribution to the orientation of humankind in the 20th and 21st century. This volume contains contributions in English, French, and German